Pengaruh stabilisator polivinil alkohol terhadap ukuran nanopartikel perak hasil sintesis dengan metode reduksi - Sumiati Side; Diana Eka Pratiwi (Seminar Nasional LP2M UNM, 2019)
Silver nanoparticles were synthesized by an environmentally friendly chemical reduction method using Moringa olifera plant extract as reducing agent for the AgNO3 precursor.. The synthesis of silver nanoparticles was carried out without and with the addition of PVA. The formation of silver nanoparticles was monitored by observing UV-Vis absorption. The results showed that the synthesis of silver nanoparticles with the addition of 1% PVA gave smaller particle size than without addition of PVA. Stirring speeds up the process of forming silver nanoparticles. Maximum absorption of UV-Vis from silver nanoparticles colloid with addition 1% PVA and without addition of PVA at wavelengths of 475 nm and 476 nm respectively in 240 minutes of storage. The purity of the silver nanoparticles synthesized was determined using the XRF instrument and the silver metal content in the synthesized powder was 89.95% with the addition of 1% PVA and 46.23% without the addition of PVA. The size distribution and nanoparticle phase were analyzed using XRD instruments and obtained the average size of the silver nanoparticles synthesized by 24.08 nm with addition of 1% PVA and 32.00 nm without addition of PVA, and both having a face centered cubic (fcc) geometry.